PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 1 SOLOK - Nurza, Nadia Fitri (Departemen Matematika, 2024)
One of the most important skills that students of mathematics are expected to develop is the ability to solve problems. Class VIII students at SMP Negeri 1 Solok continue to struggle with this area, though. Applying the Problem Based Learning (PBL) approach is one potential move. Our hope is that by following the steps outlined in the PBL model, we can better understand how these abilities develop and, ultimately, if they are more effective than those taught using more traditional methods. It is safe to call this study a pseudo-experiment. Class VIII.H and class VIII.K students from SMP Negeri 1 Solok TP 2024/2025 were chosen as the sample group for the study. As research tools, the final test and evaluation were used. While compared to those who used more traditional learning models, the results showed that the PBL significantly improved performance on all measures.Keywords– Mathematical Problem Solving Ability, Problem Based Learning Model, Conventional Learning Model